Does leaf litter from invasive plants contribute the same support of a stream ecosystem function as native vegetation?. Issue 4 (10th April 2017) - Kuglerová, Lenka; García, Liliana; Pardo, Isabel; Mottiar, Yaseen; Richardson, John S.
Abstract: Riparian habitats are highly susceptible to invasion and the spread of non‐native plants. Many freshwater organisms and processes are dependent on allochthonous subsidies, and thus, riparian invasions are often associated with changes in aquatic ecosystems. We studied the potential effects of riparian plant invasions on instream decomposition and detritivore communities. We compared decomposition rates ( k ) of leaf litter from species native and invasive to coastal British Columbia, and the macroinvertebrate assemblages associated with the local and novel resource subsidy. Five native and five invasive species of riparian plants representing various growth forms (i.e., herbs, shrubs, and trees) were used in a litter bag experiment. Litter bags were distributed in stream‐side experimental channels, ensuring similarity in background environmental conditions (substrate, flow, and temperature). Compared to native litter, the k ‐values of invasive plants were 2.6 times higher for herbs and 1.3 times higher for trees, while shrubs did not differ. Shrubs also decomposed significantly slower than trees and herbs. These patterns could be partially explained by the chemical properties of the litter. Throughout the whole experiment, decomposition rates were negatively related to the content of structural carbohydrates which tended to be higher in native leaves of herbs and shrubs. The k ‐values also had positive relationships with nitrogen content measured in the unconditioned and conditioned litter, and invasive plant species had some of the highest values of leaf nitrogen. We found no significant relationships between decomposition rates and the lignin content of the conditioned and unconditioned leaf litter. Taxonomic richness of all aquatic macroinvertebrates and densities of all aquatic macroinvertebrates and shredders were significantly higher on the invasive litter incubated for 21 but not for 53 d. Finally, richness of shredders explained the highest proportion of the variance in decomposition rates, when compared to other biological (all macroinvertebrate densities and richness) and litter chemistry variables. Our results indicate that riparian plant invasions are associated with changes in aquatic litter decomposition; however, the direction of the change is largely dependent on litter quality and plant identity rather than growth form or exotic status.